Desorption of 137Cs from Cetraria islandica (L.) Ach. using solutions of acids and their salts mixtures - ANA A. ČUČULOVIĆ (Journal of the Serbian Chemical Society, 2009)
The desorption of 137Cs from Cetraria islandica (L.) Ach. lichen was investigated using the solutions: A) H2SO4–HNO3–K2SO4, B) H2SO4–HNO3–Na2SO4 and C) H2SO4–HNO3– (NH4)2SO4–(NH)4NO3 at pH 2.00, 2.58, 2.87, 3.28 and 3.75, similar to acid rain. After five consecutive desorptions using solutions A, B and C, from 44.0 % (solution B, pH 3.75) to 68.8 % (solution C, pH 3.28) of 137Cs had been desorbed from the lichen. In all cases, the most successful 137Cs desorption was the first one. In the presence of K+ (solution A) the total amount of desorbed 137Cs did not depend on the pH of the solution and this was confirmed by the analogous reactions of Cs+ and K+, due to their similar ionic radii. The dependencies of the non-desorbed content of 137Cs on the number of desorptions gave curves indicating that at least two types of sorption occur. One of them can be dominant if suitable desorbants are used. The results indicate lichens as secondary sources of environment pollution with 137Cs.